2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.111-493
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Clinician:friendly Query Builder for Decision Support During ECG Interpretation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Experimental evaluations showed that clinicians could use ecgRuleML to define new rules and update existing rules. Cloughley, Bond [57] built a knowledgebase of thirty-eight identified ECG diagnostic interpretations constructed from online ECG library databases. The knowledgebase consists of characteristic data such as rhythm, wave, features, causes, sample images and diagnostic reports for each ECG recording.…”
Section: Knowledge-based Approachmentioning
confidence: 99%
“…Experimental evaluations showed that clinicians could use ecgRuleML to define new rules and update existing rules. Cloughley, Bond [57] built a knowledgebase of thirty-eight identified ECG diagnostic interpretations constructed from online ECG library databases. The knowledgebase consists of characteristic data such as rhythm, wave, features, causes, sample images and diagnostic reports for each ECG recording.…”
Section: Knowledge-based Approachmentioning
confidence: 99%